Alguns aspectos sobre o processo da democratização dos sistemas políticos no mundo árabe :Egito e Líbano como modelos de estudo - Haddod, Younus Khalifa (2006)
The World has tried diverse democratic waves at distinct moments. Some nations have adopted the idea of the democracy for years; others have not yet and other ones are still in a slow process of transition. The field of studies on the Arabian political systems has testified since the last quarter of 20th century a notorious development. This advance disclosed in the existence of a set of trends that has turned around a number of concepts and main theoretical frames such as the political pluralism and the democratic transition and the civil society and its relation with the State. The speech on the process of democratic transition consists in part in the capture and the analysis of the role of the forces and the organizations of the civil society in this process. The peculiarities of the Arab World excite questions concerning the establishment of one governmental system in this universe in the mold of that one that develops with hegemony in the Occident, which has become an interesting field of inquiries for the Political Science. This study comprises the analysis of some aspects of the political situation in the Arab World towards the process of democratization in which Egypt and Lebanon are models of study. Thus the theoretical basis of the term democracy is introduced, presenting different considerations about this expression, since the sprouting of the term until its current conception; later the civil society is analyzed as well as the systems of the political parties and the electoral systems of both countries in attempt to identify the level of democratization existing there and also to find the possible ways to magnify the democratic horizons